Teacher and Student Communication Model in the Independent Curriculum - Nabila; Sarianus Ndraha (Yayasan Salam Cerdas Al-Fattah, 2024)
This study aims to explore the communication model between teachers and students in the Independent Curriculum in Indonesia. The focus of the research is to understand how communication occurs in a more flexible teaching context and is based on active student engagement. The method used is an exploratory literature study by collecting data from journal articles, thesis books, and relevant PMM good practices. The data analysis technique used is triangulation to verify findings from various sources. The results of the study show that communication in the Independent Curriculum emphasizes more open and collaborative two-way interaction, with the role of teachers as facilitators who support student development. This discussion revealed the importance of a communication approach based on empathy, respect for diversity, and the development of students' critical skills through the use of technology in the teaching and learning process